Implementing 'Goals of Care' discussion and palliative care referral for patients with advanced lung cancer: an outpatient‐based pilot project. Issue 4 (22nd April 2021) - Conduit, Ciara; Thompson, Michael; Thomas, Robyn; Nott, Louise; Wuttke, Melanie
Abstract: Background: Early involvement of palliative care and advance care planning improves quality‐of‐life outcomes and survival for patients with advanced lung cancer; however, there are barriers to implementation. Aims: A single‐centre prospective audit reviewing 'Goals of Care' (GOC) form completion and palliative care referrals in an oncology clinic was undertaken with the aim of increasing GOC completion and palliative care referrals for patients with advanced lung cancer. Methods: Involved physicians attended a communication skills course and then received a communication‐priming intervention. Clinicopathological factors associated with GOC completion and palliative care referral were explored. Results: A total of 84 patients receiving palliative treatment for advanced lung cancer was enrolled. Clinicopathological factors, such as poorer performance status, were associated with higher likelihood of GOC completion ( P = 0.018) prior to the intervention. Male sex ( P = 0.023), absence of sensitising epidermal growth factor receptor mutation or anaplastic lymphoma kinase rearrangement ( P = 0.017), type of systemic therapy ( P = 0.031) and poorer performance status ( P < 0.001) were associated with higher likelihood of palliative care referral. The intervention improved GOC completion (relative risk (RR) 1.29, P = 0.004); however, this was not sustained in a follow‐up audit (RR 0.98, P = 0.92) and there was no change in palliative care referral rate (RR 2.5, P = 0.16). Predictors of palliative referral following clinical review included age (RR 1.16, P = 0.001), male sex (RR 14.2, P = 0.02) and poorer performance status (RR 1.76, P < 0.001). Conclusions: Communication‐priming interventions can improve GOC completion for patients with advanced lung cancer. Further investigation is needed to pursue sustainable options for managing this complex patient group and improve guideline‐adherence and patient care.